2012
DOI: 10.5426/larynx.24.128
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Adult-Onset Arytenoid Type Laryngomalacia Successfully Treated with a Resection of Flaccid Arytenoid Mucosa

Abstract: Laryngomalacia is one of the most common diseases of laryngeal stenosis in newborns and infants. In contrast, adult-onset laryngomalacia cases are rare and the majority of them are classified as an epiglottic type. We report on a case of 20 -year old female with arytenoid type laryngomalacia who presented with an intermittent inspiratory stridor after catching a cold. Her pulmonary function was normal; however, endoscopic examination showed an inward prolapse of the bilateral flaccid arytenoid mucosa during st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…In view of the clinical picture of endoscopic finding of short aryepiglottic fold with long epiglottis and multiple failed attempts of extubation surgery was planned in the present case. Hey et al reported adult onset laryngomalacia in 2 patients [18] , Hyodo et al reported adult onset layngomalacia in a 20 year old female [19] and in this study we report the same in 12 year old male patient. Richter et al also reported a series of late onset laryngomalacia where 17 patients were diagnosed as having laryngomalacia when they were older than 2 years(mean age at onset 6.6 years) [20] .…”
Section: Discussionsupporting
confidence: 76%
“…In view of the clinical picture of endoscopic finding of short aryepiglottic fold with long epiglottis and multiple failed attempts of extubation surgery was planned in the present case. Hey et al reported adult onset laryngomalacia in 2 patients [18] , Hyodo et al reported adult onset layngomalacia in a 20 year old female [19] and in this study we report the same in 12 year old male patient. Richter et al also reported a series of late onset laryngomalacia where 17 patients were diagnosed as having laryngomalacia when they were older than 2 years(mean age at onset 6.6 years) [20] .…”
Section: Discussionsupporting
confidence: 76%